2018
DOI: 10.1021/acsnano.7b08614
|View full text |Cite
|
Sign up to set email alerts
|

Leakiness of Pinned Neighboring Surface Nanobubbles Induced by Strong Gas–Surface Interaction

Abstract: The stability of two neighboring surface nanobubbles on a chemically heterogeneous surface is studied by molecular dynamics (MD) simulations of binary mixtures consisting of Lennard-Jones (LJ) particles. A diffusion equation-based stability analysis suggests that two nanobubbles sitting next to each other remain stable, provided the contact line is pinned, and that their radii of curvature are equal. However, many experimental observations seem to suggest some long-term kind of ripening or shrinking of the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 33 publications
5
51
0
Order By: Relevance
“…The LJ potential pair parameters used for the mW and N 2 model simulations are also shown in Table II, using similar values from past surface nanobubble simulations. 33,42,43 Potential parameters between mW molecules and the S o and S i atom types were calibrated in pre-simulations to obtain equilibrium gasside contact angles of 35 • and 99 • , respectively. Potential parameters between the nitrogen molecules and the wall atom types were calibrated to achieve similar density fluctuation Pressure was applied by the piston, with all piston atoms subjected to a mean force F z = −P ∞ A p /N, where A p is the area of the piston in the (x, y) plane, and N is the number of piston wall atoms.…”
Section: Molecular Dynamics Simulation Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The LJ potential pair parameters used for the mW and N 2 model simulations are also shown in Table II, using similar values from past surface nanobubble simulations. 33,42,43 Potential parameters between mW molecules and the S o and S i atom types were calibrated in pre-simulations to obtain equilibrium gasside contact angles of 35 • and 99 • , respectively. Potential parameters between the nitrogen molecules and the wall atom types were calibrated to achieve similar density fluctuation Pressure was applied by the piston, with all piston atoms subjected to a mean force F z = −P ∞ A p /N, where A p is the area of the piston in the (x, y) plane, and N is the number of piston wall atoms.…”
Section: Molecular Dynamics Simulation Setupmentioning
confidence: 99%
“…MD is a high-fidelity simulation technique that can model such behavior, for example, the contact line stick/slip dynamics, surface tension effects and diffusive growth, via fundamental Newtonian dynamics and chemical intermolecular potentials. 33,[41][42][43][44] The penalty of MD is its extreme computational cost, which limits the bubble sizes that can be modeled (R ∼ 10 nm) as well as the largest time scales of the dynamics (∼ 10 ns). Other techniques exist for modeling surface nanobubbles, such as lattice density functional theory, 26 and more recently with continuum-based solvers, coupling a finite difference scheme with the immersed boundary method to simulate pinned growth under various saturation conditions for µm sized surface nanobubbles.…”
Section: Introductionmentioning
confidence: 99%
“…[ 34] have revealed that in certain cases (very strong attraction between the dissolved gas molecules and the surface) surface nanobubbles very close to each other can communicate through a "new channel", namely diffusion of gas from one surface bubble to the other along the surface, and not through the bulk. If this is the case, some sort of ripening process of neighboring surface bubbles may be possible in spite of hydrodynamic stability against Ostwald ripening.…”
Section: Ray Of Bubblesmentioning
confidence: 99%
“…refs. [58,59]. The downsides of MD are that (i) only small nanodroplets (∼50 nm) can be simulated, that (ii) one is restricted to short physical times of at most microseconds, and that (iii) molecular interaction potentials are needed, which are not from first principles.…”
Section: Introductionmentioning
confidence: 99%